Penal requirement in the contracts of professional players: comparative study - لطيف, زينة قدرة; محمد, ثامر جاسم (Journal of Legal Sciences, 2019)
Sport is generally no longer merely a game of entertainment, but it is a work of the player for the sports club contracted by him. The player is no longer regarded as a means of entertainment and physical development, but is seen as an economic Which is to gain a return for the effort, and because of the spread of the phenomenon of professionalism in the field of sports, emerged sporting contracts coupled with penal conditions as a means to regulate the relationship between the player and the sports club is the contract transfer professional player and his loan, and his professional contract, which concerns us in this regard is to address the J Loyalty) contained in the contract between the player and club sports.